Jenő Bánó: Travels of an Immigrant and his Path to Diplomacy - Venkovits, Balázs (Acta Neerlandica, 2020)
This paper introduces a case study of Hungarian emigration to the Americas, which illustrates some of the general trends in migration at the turn of the century as well as a unique career path of a Hungarian immigrant in Mexico. By discussing and analyzing the life, diplomatic career, and publications of Jenő Bánó, the paper touches upon issues including the significance of travel writing in influencing migration, the use of migration propaganda, and relations between Hungary and the Americas.